2016
DOI: 10.4103/0972-6748.196050
|View full text |Cite
|
Sign up to set email alerts
|

Medical students′ attitude toward suicide attempters

Abstract: Background:Majority of health professionals have unfavorable attitudes toward the patients presenting with self-harm, which further compromises their therapeutic endeavors and outcomes.Objectives:This study was aimed to assess the medical students' attitudes toward suicide attempters.Materials and Methods:A cross-sectional study was conducted in a tertiary care medical institute of Haryana, a Northern state of India. Two hundred and five final year medical students were recruited through total enumeration meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 34 publications
2
25
0
3
Order By: Relevance
“…Furthermore, the sample was predominantly male, and one previous study noted that girls had a greater negative attitude than boys about suicide. 9 Hence, our study findings could be influenced by the sociodemographic profile.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, the sample was predominantly male, and one previous study noted that girls had a greater negative attitude than boys about suicide. 9 Hence, our study findings could be influenced by the sociodemographic profile.…”
Section: Discussionmentioning
confidence: 82%
“…It has been used in Indian studies and has been found to not only have high test-retest reliability but also good internal consistency. 9 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigmatising attitudes of health care professionals towards mental illness can impede treatment provided for patients suffering from psychiatric problems. 6 N. Nebhimani et al 7 in their study among final year medical students in Haryana, found that only one-third of the students had favourable attitudes towards suicide attempters. M. Nebhimani et al 8 had conducted a similar study among nursing students and found favourable attitudes towards suicide attempters in the majority of students.…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the first, the majority of health professionals have unfavorable attitudes toward patients' self-harm, which might compromise their therapeutic endeavors and outcomes. Several studies have investigated this topic in medical students, using different tools (Oncü et al, 2008 ; Palmieri et al, 2008 ; Yousuf et al, 2013 ; Chan et al, 2014 ; Hashimoto et al, 2014 ; Nebhinani et al, 2016 ), and have suggested an association between medical students' attitudes toward suicide and appropriate therapeutic responses to suicidal individuals (Hashimoto et al, 2014 ). Students' knowledge and attitudes toward suicide have been described as changing during the years of training.…”
mentioning
confidence: 99%